Visceral larva migrans among children in Kütahya (Turkey) and an evaluation of playgrounds for T. canis eggs - Akdemir, Cihangir (The Turkish Journal of Pediatrics, 2010)
This research was undertaken to determine the seroprevalence of Toxocara canis (T. canis) in children aged 3-13 years in Kütahya, to determine the presence of infected larvae in playground sandboxes, and to obtain a view of the general situation regarding visceral larva migrans (VLM) in the city. The blood sera of 119 children (54 girls, 65 boys) were tested for T. canis IgG, and 9 (7.6%) were found positive. In sand samples collected from playgrounds in nine different residential areas across the city, only two of them, in Inköy and Zafertepe neighborhoods, had T. canis larvae; in total, 3 of the 30 sand samples (10%) contained larvae. It is concluded that the main factor regarding VLM infection in children is outdoor playgrounds or playing areas.